Accounting Information Quality and Lending Decision Making Processes (gjstudies, 2018)
This research investigates the nuanced relationship between accounting informationquality (AIQ) and lending decision-making processes, proposing a novel conceptualframework that integrates cognitive psychology, information theory, and institutionaleconomics. While prior literature has predominantly examined AIQ through quantitative metrics of earnings management or accrual quality, this study introduces amultidimensional construct that captures both objective verifiability and subjectiveinterpretability dimensions of accounting information. We develop and test a processoriented model that traces how different AIQ dimensions influence sequential stages oflender cognition—from initial screening to final covenant structuring—using a mixedmethods approach combining experimental simulations with archival loan data analysis. Our findings reveal that lenders do not respond uniformly to AIQ dimensions;rather, their sensitivity varies systematically with decision stage, institutional context,and individual expertise. Specifically, we document that verifiability metrics primarilyaffect early screening decisions, while interpretability factors dominate later negotiationstages. Furthermore, we identify a previously unrecognized ’compensatory heuristic’whereby lenders substitute between AIQ dimensions when making trade-offs underuncertainty. The study contributes to accounting, finance, and decision sciences byproviding a more granular understanding of how information quality shapes financialintermediation, offering practical implications for standard-setters seeking to enhancethe decision-usefulness of financial reporting and for financial institutions aiming tooptimize their credit evaluation protocols. Our cross-disciplinary approach bridgesmethodological divides between experimental and archival research traditions, demonstrating how cognitive processes mediate the relationship between information characteristics and economic outcomes.